2014
DOI: 10.1186/1471-2156-15-s1-s9
|View full text |Cite
|
Sign up to set email alerts
|

Single-base-resolution methylomes of populus trichocarpa reveal the association between DNA methylation and drought stress

Abstract: BackgroundDNA methylation is an important biological form of epigenetic modification, playing key roles in plant development and environmental responses.ResultsIn this study, we examined single-base resolution methylomes of Populus under control and drought stress conditions using high-throughput bisulfite sequencing for the first time. Our data showed methylation levels of methylated cytosines, upstream 2kp, downstream 2kb, and repeatitive sequences significantly increased after drought treatment in Populus. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(120 citation statements)
references
References 44 publications
6
111
2
1
Order By: Relevance
“…The present MSAP profiling showed that the global level of methylation level was somewhat (about 6.58%) higher in the R2 than in the R1 material. A number of environmental stresses have been suggested as being able to induce alterations in DNA methylation profiles (Dowen et al, 2012;Liang et al, 2014). In some cases, the stress lowers methylation -such as stress by drought in Lolium perenne and cold in Cicer arietinum L. Rakei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present MSAP profiling showed that the global level of methylation level was somewhat (about 6.58%) higher in the R2 than in the R1 material. A number of environmental stresses have been suggested as being able to induce alterations in DNA methylation profiles (Dowen et al, 2012;Liang et al, 2014). In some cases, the stress lowers methylation -such as stress by drought in Lolium perenne and cold in Cicer arietinum L. Rakei et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…There are many documented effects of DNA methylation on plant phenotype, which has an impact on the response to various biotic and abiotic stresses (Li et al, 2012a;Liang et al, 2014;Naydenov et al, 2015). Certain stresses which disturb plant growth and development have been shown to induce alterations in the pattern of methylation of genomic DNA (Ding et al, 2014;Zhong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gene-body DNA methylation is extensive in the open chromatin state, linked to structural gene characteristics (gene size and copy number) and correlated with tissue-specific gene expression Lafon-Placette et al 2013;Vining et al 2013). DNA methylation is also involved in regulating stress response genes (Liang et al 2014;Maury and Lafon-Placette, unpublished data). In addition, the methylation patterns of the parents are partially and dynamically passed onto their hybrid offspring (Gao et al 2014).…”
Section: Epigenomics In Trees: a New Dimension To Phenotype Predictiomentioning
confidence: 97%
“…DNA methylation is closely related to gene expression, and it appears that different methylated regions in genes have different effects on gene expression (Lou et al, 2014). In Populus trichocarpa, methylation of 100 bp upstream of the TSS (transcriptional start site) represses gene expression, while methylation in 100-2000 bp upstream of TSS and within the gene body are positively associated with gene expression (Liang et al, 2014). Methylation in the gene promoter region has long been considered a suppressor of gene expression (Su et al, 2011).…”
Section: Relationship Between Gene Body Methylation and Expression Ofmentioning
confidence: 99%